Assessing sustainable energy development in the central and eastern European countries and analyzing its diversity - Brodny, Jarosław; Tutak, Magdalena (The Science of the total environment, 2021)
The growing social awareness of environmental protection entails that the assumptions of the sustainable development idea are being implemented in various economic sectors at an increasingly fast pace. One of them is the power industry, the sustainable development of which is now becoming a priority in economic policy for many countries. The paper refers to this issue by developing methodology for both studying and assessing the level of sustainable energy development in the Central and Eastern European Countries. The study involved 21 indicators characterizing the sustainable energy development of these countries in the areas of energy, environmental, economic, and social security for 2008 and 2018. When considering the complexity of the subject matter and the wide scope of the research, four methods of multi-criteria data analysis (TOPSIS, VIKOR, MOORA and COPRAS) were used. For each of them, based on the adopted criteria, synthetic indicators were determined, which allowed for the assessment of the level of sustainable energy development in the CEE countries. Weights for the adopted indicators were identified based on the Shanon's Entropy method. Afterwards, an unambiguous assessment of the level of sustainable energy development of the CEE countries was performed. The results showed that in 2008 and 2018, the best ranking position was held by Latvia and Croatia, and the worst ranking position was held by Poland and Bulgaria. The method of multidimensional scaling made it possible to determine the positions of studied countries on scatter plots in two-dimensional space, which showed differences between individual CEE countries. All in all, the applied methods allowed for a considerably broad assessment of the level of sustainable energy development of the CEE countries. [Display omitted] •A SED evaluation system which consists of 21 indicators is presented.•The Shannon Entropy methods is used to obtain weights of indicators.•MCDM’s were used for the assesing sustainable energy development.•Multidimensional scaling was used for the assesing diversity CEE-11 countries.•In 2008 and 2018, the best level is in Lithuania and the worst - in Bulgaria.